FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN KANKER KEPALA DAN LEHER - Alanis Maryjane Mamahit (2023)
Head and neck cancer is a cancer that is still commonly found in the world with an incidence of more than 550,000 new cases and 300,000 deaths each year. Approximately 90% of head and neck cancers are a type of squamous cell carcinoma, which ranks sixth in the world's cancer incidence. Two-thirds of head and neck cancer cases occur in developing countries, where Indonesia itself, which is a developing country, has a relatively high prevalence of head and neck cancer with an incidence of 4.7/100,000 population. The safety rate and quality of life of head and neck cancer patients is highly dependent on the factors that determine the patient's prognosis, one of which is knowledge to initiate prevention and early prevention. There are several factors that can affect one's knowledge. Among them include age, level of education, occupation, interests, experience, environment, and sources of information. Knowing the factors associated with knowledge of head and neck cancer. This study aims to determine the factors associated with knowledge of head and neck cancer. Methods: A cross-sectional survey was conducted in RW 06 Nyiur Melambai Complex, Rawa Badak Utara sub-district, Koja District, North Jakarta. Questionnaires were given to 60 respondents. The questionnaire assesses the factors that influence a person's knowledge of head and neck cancer. Statistical descriptive analysis was used for this study and the relationship between demographic variables and knowledge was analyzed by chi-square test and multivariable logistic regression. Results: The knowledge of respondents who reported having a high level of knowledge (71.2%), this level of knowledge did not have a significant relationship to the age factor (p=0.286), educational level factor (p=0.779), employment level factor (p= 0.790), the source of information factor (p=0.580) for residents of RW 06 Nyiur Melambai Complex, Rawa Badak Utara Village, Koja District, North Jakarta. Conclusion: Factors that influence knowledge such as age, education level, occupation and information sources are not related to knowledge of head and neck cancer in RW 06 Komplek Nyiur Melambai, Rawa Badak Utara subdistrict, Koja District, North Jakarta.